The Implementation of Management Audit As A Means To Assess The Effectiveness Of The Human Resource Management Function At PT. Gresik Cipta Sejahtera Makassar Branch - Tita Anggriani (Journal AGENCY, 2022)
This study aims to identify and analyze the application of management audits as a means of assessing the effectiveness of the human resource management function at the PT Gresik Cipta Sejahtera Makassar branch. This qualitative research uses research by looking at the application of management audits as a means of assessing the effectiveness of the HRM function at PT. Gresik Cipta Sejahtera Makassar Branch. Data collection methods used were observations, interviews and documentation. While the data analysis technique used is a descriptive analysis method by assessing the effectiveness of personnel functions based on a comparison between conditions, criteria, causes and effects. The results show that the application of management audits as a means of assessing the effectiveness of the prestige of human resource management is by evaluating employee performance and ensuring that each employee carries out his duties and responsibilities according to his job, and that management conducts training and assessments in the procurement of human resources. company.